A DESCRIPTIVE STUDY OF THE PLATFORM OF ALGERIAN MANUSCRIPTS - Tahar Abbou (Asian and African Studies)
Manuscripts represent a vital cultural and intellectual heritage, with Algeria recognized as a key custodian due to its numerous Libraries (traditional libraries) dispersed nationwide. This study pre sents the establishment of the Platform of the Algerian Manuscripts, designed to centralize and facilitate access to this rich heritage. The article outlines the Platform’s objectives, introduces the dedicated research team responsible for cataloguing and digitizing manuscript data, and provides statistical information on the Platform’s contents, including thematic coverage, authorship, and the traditional libraries surveyed. Furthermore, it highlights several rare manuscripts featured on the Platform. The discussion emphasizes the Platform’s significance for researchers, illustrating its po tential to advance manuscript-related scholarship and preservation efforts in Algeria.